POLA PENGEMBANGAN INDUSTRI MANUFAKTUR DI INDONESIA, 1976-1993 - LINCOLIN ARSYAD; ARYA DETAJANNA (Faculty of Economics and Business, Universitas Gadjah Mada, 1997)
This paper mainly analyses the growth of industrialisation in Indonesia.Industrialisation initially began with the protective strategy of import substitution industries, which eventually grew into export oriented manufacturing, especially in response to the drop in international oil prices (1986). The next analyzes leads to evaluating the extent of influence demonstrated by capital intensived industry and labor intensive industry in increasing national income during the period of 1976-1993- To be more spesific, both periods of 1974-1984 and 1985-1993 are analyzed base on the contribution of labor intensive industry to thegrowth of income and the contribution of capital intensive industry to import substitution industries- An additional protion on the growth pattern of compound industries will be outlined, citing cases from several countries, including analytical findings in Indonesia. In order to provide a clearer outlook of analytical findings in Indonesia, Industry indicator data will be classified into several groups. Another important part is significance testing of certain industries in taking advantage of economic scale using a set of tools, mainly the textile, paper, glass, cement, basic metal in addition to labor intensive industries in Indonesia. This paper will be ended with a conclusion which stresses requirements demanded in order to achieve a growth pattern in compound industries in a certain country along with the implications caused by the chosen policy.